The Virtuosity of Traditional Africa and the Plasticity of Its Affects: The Cross-Cultural Fertilization of “Yela” in the Western Sahel and Savanah - Souleymane Diallo (Borong Newinera Publisher, 2022)
Throughout the poetic image and imaginative construction of the self, the Yela embodies a protrusive source of vindication within the intellective and creative process of understanding become an object of perception. From an ingenuous beget to a more compound whole of a convention of representation and the association of experience, the Yela inside the Puular language becomes a structural material. Thus, the constituent of conservative imagery and the colonialist dynamic influences frame an innovative eccentric variety that appraises the formation of reality, memory, and symbol. Therefore, the domain of Yela through its cultural and artistic body, and within its existing essentiality of Gaandal and Demngal overtakes the principles of basic linguistics and the colonialist conventional perception of productivity. In effect, the Yela art through the all-encompassing relation of the Puular language with the whole performance of time and space, emphasizes on a cosmopolitan wholesome recombination, settlement and re-appropriation of material imagination and objective reality of intellection. The foundation of intellectual and artistic image, and imaginative expression, the corresponding inventiveness of the Yela art, and the musical nationalism arrange move beyond comatose understanding. Therefore, the commitment of this article underlines the question of the effective temperature of the Yela indigenous value of imagination, and its transformative experience as regard language, sociolinguistic and ecological reflectivity, and then its emphasis on its contemporary stylistic compass of performance.